PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA PELAJARAN IPAS TERDIFERENSIASI DI KELAS IV - Julia Adenti; Ryan Dwi Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research investigates how the Problem Based Learning (PBL) model affects student engagement and comprehension in Science and Social Studies (IPAS) for fourth graders at UPTD SD Negeri 47 Gedong Tataan. Employing a two-cycle Classroom Action Research (CAR) design—each involving planning, execution, observation, and reflection—this study included 20 participants during the second semester of the 2024–2025 academic year. A validated set of multiple-choice tests was administered before and after the implementation of PBL. The results demonstrate a significant improvement in students' academic performance and active involvement. The mean score rose from 68.5 to 86.25, while the mastery rate increased from 40% to 95%. In addition to academic gains, students also displayed better teamwork and critical thinking skills. The findings underline the potential of combining PBL with differentiated instruction to build an inclusive and effective classroom environment. Therefore, adopting this integrated model is strongly recommended for primary-level IPAS education.